Perancangan dan Pemanfaatan Digital Marketing untuk Meningkatkan Sektor Perekonomian Masyarakat Desa Gambirono - Didik Pudjo Musmedi; Kristian Suhartadi Widi Nugraha; Nanda Fatimatuzzahrah; Ketut Indraningrat; Eka Bambang Gusminto (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The lack of knowledge of the people of Gambirono Village about digital technology for business development is one factor in the unstable economy of Gambirono Village. The Gambirono community still really needs digital marketing assistance and training. This community service activity aims to increase the understanding of the Gambirono Village community about digital marketing and train the Gambirono Village community in the use of e-commerce and social media as a means of entrepreneurship, especially during this pandemic. The method used is the community development pillar approach, namely participation, institutionalization, and sustainability. In addition to the general problems faced by the people of Gambirono Village, the community service team has also developed a financial information system for convection business actors who during this pandemic have experienced difficulties in controlling the entry and exit of finances due to uncertain money. enter. In addition, the activities carried out are conducting door to door training on the use of e-commerce and social media in the surrounding community